Investigation of rapid-starting strategy of cold start processing on porous medium-catalyst hybrid reformer. (14th September 2015) - Lai, Ming-Pin; Horng, Rong-Fang; Lai, Wei-Hsiang; Chao, Pin-Chun; Chen, Chen-Yu
Abstract: This study investigated the control strategy for the rapid cold startup process in porous media-assisted (PM-assisted) catalyst hybrid reformers that produce syngas from the partial oxidation of methane (CH4 ). A control strategy was established based on the axial temperature distribution and infrared thermal imaging observations of the reformer under total oxidation reaction. In this study, methane was used to explore the temperature fluctuation characteristics exhibited by various fuels (CH4 or H2 ) during the startup process in reformer. Methane was also used to investigate operational strategies for achieving rapid cold-startup. The experiments confirmed that the rapid flame propagation speed and small quenching distance of hydrogen can shorten the startup time, reduce chemical energy supply, and provide superior thermal stability. The experimental analyses indicated that PM-assisted cold startups can improve the thermal stability of catalyst beds, reduce the temperature fluctuations in reformed gases, and effectively increase the reactive temperature of catalyst-packed beds. Highlights: The rapid-starting strategy of cold start processing was established. A porous media-assisted catalyst hybrid reformers for reforming was studied. Thermal imaging of the reformer during the startup process was observed by infrared thermograph.